Fabrication and characterisation of graded index nanostructured TiO2 compact layers for dye-sensitized solar cell / Mohd Hanapiah Abdullah - Abdullah, Mohd Hanapiah (Institute of Graduate Studies, UiTM, 2015)
A novel graded index nanostructured TiO2 compact layer (arc- TiO2) had been successfully deposited on Indium tin oxide (ITO) substrate by long-throw radiofrequency (RF) magnetron sputtering. The main aims of the arc-TiO2 compact layer were to serve as an antireflective compact layer that could reduce reflection losses, improve the photo-response of dye molecules, and prevent electron recombination in a dye-sensitized solar cell (DSSC) application. The employment of the TiO2 compact layer in the DSSC was carefully optimised in term of RF power and thickness of the arc-TiO2 film. Meanwhile, the desired characteristics were systematically investigated by means of UV-absorption spectra, incident photon to current efficiency (IPCE), open-circuit voltage decay (OCVD) and electrochemical impedance spectroscopy (EIS). The average transmittance of the ITO/arc-TiO2 conducting substrate in the region from 400 nm to 1000 nm was approximately 85%. Corresponding average reflectance difference that was recorded in comparison to the bare ITO was 2.5 %. The red-shift behaviour of the transmittance peak was actually due to the formation of a new hybrid band energy structure of 3.1 eV resulting from the tin (Sn) diffusion in the ITO film that shifted the absorption edge of the substrate. This had favoured the absorption characteristics and photo-response of N719 dye…